MAXIMIZING BENEFITS FROM NETWORK COLLABORATION: HOW ORGANIZATIONS EXPLOIT NETWORK RELATIONS IN HIGHLY UNPREDICTABLE ENVIRONMENTS - Flieger, Marcin (Management and Administration Journal, 2024)
The main scientific purpose of this article is to identify how organizations maximize benefits from network relations in highly unpredictable environments, including both operational and strategic perspectives of network collaboration. The study is designed to deepen our knowledge about the nature of inter-organizational networks, and our understanding of the dynamics of relations between actors and the possibilities of exploiting networks in order to maximize benefit (network and relational rent). The research was carried out using the interpretative method of a multiple case study, following methodological rigor. It was divided into two stages: case-study analysis and cross-case analysis. The research shows that in highly unpredictable environments, when  organizations have to face sudden and considerable unfavourable changes in operating conditions, they intensify relations’ features and at the same time modify expected benefits (including both operational and strategic perspective). The results allow for the identifying a pattern which shows how organizations modify the intensity of network-relation features in order to gain established benefits. The template serves as a tool for practitioners who can use it in planning and developing interactions with other members of networks (knots).